PLAYING THERAPY CAN REDUCE POST TRAUMATIC STRESS DISORDER (PTSD) IN POST-EARTHQUAKE CHILDREN - Dr. EVA YULIANI; Dr. SASTRIANI; Dr. Irfan; Dr. ACO MURSID; IKA MUZDALIA; HASRIATI (International Journal of Multidisciplinary Research and Studies, 2022)
Earthquakes lead to Post Traumatic Distress Disorder (PTSD), which is psychological stress trauma after a disaster. Management of PTSD in children is playing therapy. This study aimed to determine the effect of Playing Therapy on Post Traumatic Stress Disorder(PTSD) in children aged 7-12. This research was an experimental research with one group pre-test and post-test design. Thirty-five respondents had PTSD symptoms after the earthquake in Malunda, Majene. The research instrument used was a questionnaire. This study found a significant decrease in PTSD, with p-value = 0.001 = 0.05. It can be concluded that playing therapy affected decreasing Post Traumatic Stress Disorder (PTSD) in children aged 7-12 years who were the earthquake victims in Mekkatta Village, Malunda District.